(untitled) (Revista de Medicina Clinica, 2020)
Introduction: Atrial Myxomas (AM) are an infrequent cause of cerebral infarction (CI), primarily in young patients. Embolic CI are its main neurologic presentation form. Our aim is to show the diagnostic approach of a CI as a first manifestation of an MA in a young patient. Clinical case: A 17 years old woman without relevant medical history is admitted in the emergency room. She has a 12-hour history of sudden headache, hemicorporal left weakness, right mouth droop and vomit. In the initial neurologic examination, a complete left proportioned pyramidal syndrome was found. A head computed tomography (CT) showed a CI in the territory of the right middle cerebral artery (rMCA). An angio-tomography (angio-CT) confirmed an obstruction in its M1 portion. Since the patient presented neurologic deterioration despite general support measures, a decompressive craniectomy was performed. The patient was in the ICU for 12 days and was discharged when she showed clinical improvement. A transthoracic echocardiogram revealed a mass suggestive of an AM, which was confirmed by histopathology. After a one year follow-up, the patient exhibited neurologic improvement and a modified Rankin Scale was 4. Discussion: AM are the most common benign cardiac tumors. Although neurologic manifestations are not the most frequent, this case illustrates the relation between AM and CI in a young patient. Conclusion: CI in the young patient could be the debut clinical presentation of an AM; thus, an echocardiogram is mandatory in this group of patients. Key words: atrial myxoma, cerebral infarction in the young patient, echocardiogram.